The mandarin's tale - Denman, Roy, 1924- (London : Politico's, 2002)
"Starting in the lowly position of Assistant Principal in the Statistics Division of the Board of Trade in 1948, Roy Denman climbed the ladder to become one of the most influential civil servants in Whitehall, working closely with such political giants as Harold Wilson ('his intelligence differed from that of anybody else I had ever met in the way a super-computer differs from an abacus') and Tony Crosland ('a Cavalier among the Roundheads'), and finding himself at the epicentre of many of the big political moments of the 1960's and 1970's - notably as part of the team which negotiated British entry into Europe in the early 1970's."--BOOK JACKET.
Machine derived contents note: 1 Joining the Guild 5 -- 2 Apprentice 16 -- 3 Journeyman 62 -- 4 Master 110 -- 5 A Greater Guild 181 -- 6 Impressions, Reflections, Conclusions 246 -- Index 277.
Includes bibliographical references (p. 276) and index.
Keywords: Civil service -- Great Britain